(untitled) - Meeks, Linda (Blacklick ( U.S.A ), 1997)
Unit 10 outlines emergency care procedures that reflect the standard of knowledge and accepted practices in the United States at the time this book was published. It is the teacher's responsibility to stay informed of changes in emergency care procedures in order to teach current accepted practices. The teacher also can recommend that students gain complete, comprehensive training from courses offered by the American Red Cross.
Keywords: Health education,Public health; United States